Proses Pengambilan Keputusan Dokter - - Moordiningsih; - Faturochman (Jurnal Psikologi, 2006)
Physician decision making has an important impact on patient’s recovery and rehabilitation. A qualitative research of decision making process was conducted to explore how physicians arrive at a diagnosis decision. The informants were 11 skilled physicians who interviewed and participated in in-depth interview and observation. Data from interviews with physicians were used to construct and examine theories of decision making. The study found that decision making process would be better if supported by self-sensitivity, clear information, good standard operation procedure, alternatives availability of choices, adequate emotions, meaningful experiences, and good team-work. This study also found that algorithmic model encouraged the decision maker to think systematically and follow a logical sequence through decision making process. Bayesian model that based on probability theory had limitations on applications. The discussion suggests that second generation theories of behavioral decision can be chosen. Keywords: decision making-physician-qua-lita¬tive research